Herpes Simplex Virus Hepatitis: A Presentation of Multi-Institutional Cases to Promote Early Diagnosis and Management of the Disease. (1st August 2017) - Natu, Ashwinee; Iuppa, Guiseppe; Packer, Clifford D.
Abstract : Objective. To compare three cases of Herpes simplex virus (HSV) hepatitis to increase early diagnosis of the disease. Case 1. A 23-year-old man with Crohn's disease and oral HSV. HSV hepatitis was diagnosed clinically and he improved with acyclovir. Case 2. An 18-year-old G1P0 woman with transaminitis. Despite early empiric acyclovir therapy, she died due to fulminant liver failure. Case 3 . A 65-year-old woman who developed transaminitis after liver transplant. Diagnosis was confirmed by biopsy and she had resolution of acute liver failure with acyclovir. Conclusion . It is imperative that clinicians be aware of patients at high risk for developing HSV hepatitis to increase timely diagnosis and prevent morbidity and fatality.